Beyond the 'Geo' in Geopolitics: The Digital Transformation of Power. Issue 6 (26th May 2022) - Dear, Keith
Abstract : In this article, Keith Dear argues that demographic and geographic constraints on national power are reducing in two ways. First, that automation, robotics and AI reduce states' dependence on people to create wealth and to scale military forces to deter or fight. Second, while geography was once the only arena for international competition, today, economic, military and political contests increasingly extend to the digital metaverse. He argues that we are moving beyond the 'geo' in geopolitics, witnessing the digital transformation of power.◼